Optimizing Employee Performance Evaluation System for Performance-Based Bonus Allocation in DF Company - Adnan Zulkarnain; Saputri, Cica Nanda Trisna (Journal of Indonesian Economic Research, 2024)
In today's highly competitive business environment, accurate and effective employee performance appraisal is crucial for companies to enhance productivity and achieve organizational goals. However, DF Company, operating in a dynamic sector, faces challenges with its existing performance appraisal system, including a lack of objectivity and a limited link between appraisals and bonus awards. These issues can lead to unfairness, employee dissatisfaction, and reduced motivation. To address these challenges, this research aims to optimize DF Company's Employee Performance Evaluation System for bonus determination. Through in-depth interviews, potential problems were identified, and a structured problem-solving plan was developed. Proposed solutions include incorporating additional assessment elements such as closing rate and attendance, using appropriate Key Performance Indicators (KPIs), and developing a web-based performance appraisal application. The application was successfully developed, demonstrating accurate appraisal calculations and an intuitive user interface. The research findings highlight the potential of the optimized system in improving fairness, objectivity, and the linkage between performance appraisals and bonus awards. This can lead to increased employee motivation, satisfaction, and overall performance, facilitating talent retention and attraction in a competitive industry. While this study focuses on DF Company, further research is needed to generalize the findings to other organizations.